Accessibility and urban mobility by bus in Belo Horizonte/Minas Gerais – Brazil. (May 2019) - Lessa, Daniela Antunes; Lobo, Carlos; Cardoso, Leandro
Abstract: Accessibility and mobility are fundamental conditions of urban life today, which reinforces the need to evaluate the dynamics of access to and use of the public transport system in large cities that have experienced serious traffic and congestion problems. The present article analyses the levels of accessibility by bus in the city of Belo Horizonte / MG, including its relationship with the levels of urban mobility. To this end, accessibility indicators for bus and the mobility of the population are proposed. In addition, indicators of global and local regression models were evaluated, considering accessibility as an explanatory variable. In general, the results indicate a strong regional variation in the municipality of Belo Horizonte and suggest that accessibility to public transport by bus does not directly lead to effective mobility. Some regions have a greater discrepancy between the levels of accessibility and mobility, especially those located in peripheral areas where access to the bus transport system is lower than expected by the methodology, given the existing levels of mobility. The results, albeit essentially exploratory, may be useful to support the formulation of constructive measures, in order to minimize possible distortions in the provision of accessibility, encouraging the best use of mobility opportunities in urban space. Highlights: The SIG as a tool to aid the management of public transport. The methodological possibilities of the GWR to analyze the efficiency of the urban bus system. The potential of aggregate indicators and indices in assessing accessibility and mobility. Accessibility as a possibility and not as a condition of mobility. The need to overcome inequalities in urban accessibility.